2021
DOI: 10.1021/acsnano.1c04909
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Emission Pathways in Copper Indium Sulfide Quantum Dots

Abstract: Semiconductor copper indium sulfide quantum dots are emerging as promising alternatives to cadmium-and lead-based chalcogenides in solar cells, luminescent solar concentrators, and deep-tissue bioimaging due to their inherently lower toxicity and outstanding photoluminescence properties. However, the nature of their emission pathways remains a subject of debate. Using lowtemperature single quantum dot spectroscopy on core−shell copper indium sulfide nanocrystals, we observe two subpopulations of particles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…[ 6 ] Recently, it was reported by Lounis and co‐workers that one subpopulation of the core/shell CuInS 2 /ZnS SNCs exhibited extremely sharp PL linewidths arising from the radiative recombination of band‐edge excitons, while another population in the same ensemble exhibited a broad PL ascribed to the radiative recombination of a band‐edge electron with a defect‐assisted self‐trapped hole. [ 138 ] Another strategy to narrow the PL FWHM is to develop shelling strategies aimed on avoiding intrabandgap defects. Torimoto and co‐workers found out that amorphous InS x and GaS x shells effectively narrowed the PL linewidths of AgInS 2 SNCs down to ≈24 nm, while blue‐shifting the emission peaks due to the occurrence of band‐edge transition rather than original defect emission.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 6 ] Recently, it was reported by Lounis and co‐workers that one subpopulation of the core/shell CuInS 2 /ZnS SNCs exhibited extremely sharp PL linewidths arising from the radiative recombination of band‐edge excitons, while another population in the same ensemble exhibited a broad PL ascribed to the radiative recombination of a band‐edge electron with a defect‐assisted self‐trapped hole. [ 138 ] Another strategy to narrow the PL FWHM is to develop shelling strategies aimed on avoiding intrabandgap defects. Torimoto and co‐workers found out that amorphous InS x and GaS x shells effectively narrowed the PL linewidths of AgInS 2 SNCs down to ≈24 nm, while blue‐shifting the emission peaks due to the occurrence of band‐edge transition rather than original defect emission.…”
Section: Discussionmentioning
confidence: 99%
“…[ 136,137 ] On the other hand, in a recent study by the Lounis group, the defect‐assisted self‐trapping of the holes was revealed to be the origin of broad PL from one subpopulation of CuInS 2 /ZnS SNCs. [ 138 ]…”
Section: Synthesis and Optical Properties Of Nir‐ii Emitting Sncsmentioning
confidence: 99%
See 3 more Smart Citations